Penyelenggaraan Pembelajaran Baca Tulis Al-Qur’an (BTQ) dengan Metode Al-Nahdliyah di IAIN Tulungagung - Hidayat, Nurul (Ta'allum: Jurnal Pendidikan Islam, 2020)
IAIN Tulungagung is one of the PTKIN who has a vision of "the formation of an academic community based on the principles of science, morality, culture, and the spirit of Islam rahmatan lil 'naturalin. New students must follow the Madrasah Diniyah (Madin) activities to learn and deepen the knowledge of the Islamic religion. It is seen that IAIN Tulungagung students have various levels of understanding of Islamic knowledge, ranging from those who cannot read the letters of the Qur'an to those who can read the yellow book. Because of that, IAIN made Madin program, one of which was the learning program of Reading and Writing Al-Qur'an. This research method used descriptive qualitative research with a percentage. Data collection techniques used were interviews, observation, documentation and questionnaires. Based on research with qualitative data analysis on the focus of the problem of how the organization of reading and reading Al-Qur'an with the Al-Nahdliyah method, the results were obtained that 1) the reasons for selecting students to follow BTQ learning in the most order were a) because they felt unable to read Al -Qur'an properly and correctly, b) because they wanted to deepen BTQ, c) because it was told by parents / guardians. 2) The BTQ learning begins at 07.00 to 08.30 Monday to Thursday. Before the implementation, the BTQ coordinator determined the cleric who was teaching. 3) Evaluation of BTQ learning results from 2,734 people, who passed 2,297 people or 84%, passed conditional 138 people or 5%, and did not pass 290 people or 11%. 4) The inhibiting factors and the solution was the inhibiting factors of BTQ learning, namely low motivation from students and lack of student discipline. The solution is by explaining the importance of BTQ learning.